2007
DOI: 10.1111/j.1538-7836.2007.02576.x
|View full text |Cite
|
Sign up to set email alerts
|

Tissue factor around dermal vessels has bound factor VII in the absence of injury

Abstract: Summary. Background: ÔIdlingÕ or ongoing low-level activity of the tissue factor (TF) pathway is a postulated mechanism by which the coagulation process can become active without a lag period at sites of injury. Objective: To determine whether TF around cutaneous vessels has bound factor VIIa in the absence of injury, and thus could participate in the idling process. Methods: Immunostaining of mouse skin with antibodies against a 15-residue peptide from the sequence of mouse TF, and against the whole extracell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
63
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 28 publications
(28 reference statements)
0
63
1
1
Order By: Relevance
“…Notably, in a study of rhFVIIa secondary prophylaxis in hemophilic patients with inhibitors, patients receiving daily rhFVIIa infusions for 3 months, followed by a 3-month postprophylaxis period, showed clinical benefits even in the postprophylaxis period. 46 Previous mouse studies suggested that rhFVIIa is transported via an EPCR-dependent mechanism to the extravascular space, 18 where it can persist for extended periods of time in complex with TF, 47 potentially preventing minor bleeds before they escalate. Such mechanism may explain the prolonged clinical benefits of rhFVIIa prophylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, in a study of rhFVIIa secondary prophylaxis in hemophilic patients with inhibitors, patients receiving daily rhFVIIa infusions for 3 months, followed by a 3-month postprophylaxis period, showed clinical benefits even in the postprophylaxis period. 46 Previous mouse studies suggested that rhFVIIa is transported via an EPCR-dependent mechanism to the extravascular space, 18 where it can persist for extended periods of time in complex with TF, 47 potentially preventing minor bleeds before they escalate. Such mechanism may explain the prolonged clinical benefits of rhFVIIa prophylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, hFVIIa activity of 34% has been reported in human lymph fluid that bathes the extravascular space (20). More pertinent to this study, the presence of mFVIIa has previously been demonstrated in the perivascular space outside dermal vessels even in the absence of tissue damage (21).…”
Section: Figurementioning
confidence: 99%
“…In one view of normal hemostasis, Tf is sequestered outside of blood vessels (12)(13)(14)(15), requiring disruption of blood vessel integrity to exert its effects, and within circulating blood cells, requiring specific signaling events to promote its intravascular expression (16,17). If a sufficient Tf challenge is presented, a full coagulant response follows; if the Tf challenge is insufficient, the procoagulant response is arrested, primarily by the activity of the stoichiometric inhibitor Tf pathway inhibitor (TFPI) (18).…”
mentioning
confidence: 99%